If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 7 = -19 + -9x Reorder the terms: 7 + 4x = -19 + -9x Solving 7 + 4x = -19 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 7 + 4x + 9x = -19 + -9x + 9x Combine like terms: 4x + 9x = 13x 7 + 13x = -19 + -9x + 9x Combine like terms: -9x + 9x = 0 7 + 13x = -19 + 0 7 + 13x = -19 Add '-7' to each side of the equation. 7 + -7 + 13x = -19 + -7 Combine like terms: 7 + -7 = 0 0 + 13x = -19 + -7 13x = -19 + -7 Combine like terms: -19 + -7 = -26 13x = -26 Divide each side by '13'. x = -2 Simplifying x = -2
| -3.3+6.5=1.55 | | 10.7w+4=47.87 | | 9x+7=6x | | 6.2x+3.7=22.3 | | 6x+16=14x-80 | | 9x-(4x-3)=11+2(2x-7) | | 36*x+5= | | 36*36= | | 0.3(0.2x+1)=0.4(0.5x-1) | | 6.5Y-15=4Y+3.4 | | .3(.2+1)=.4(.5-1) | | 1/5(3x-0.5)+1/6=x/5+0.5 | | 2Z-4=8-Z | | 3Z-4=8-Z | | (x-9)/9-(x-7)/7=x | | (4x+3)/5-(7x-3)/6=0 | | 5x+4=4x+5 | | (x-1)/2+(x-2)/7=x-4 | | x+3=2x-7 | | 5(X-7)=3(X-4)-13 | | (-1,4)+x=(2,4) | | x/4-1=9 | | 6X^2-18X+24=0 | | 20x-4=8x+12 | | 6J=-15 | | 6J=-15 | | 50=2x+10 | | x^2+4x-72=0 | | x^2+4x-72=o | | x.5=8.x | | 3-x=x-1 | | 7-2(3m+6)= |